Characterizing the Influence of Water on Charging and Layering at Electrified Ionic‐Liquid/Solid Interfaces. Issue 12 (14th July 2015) - Cheng, Hsiu‐Wei; Stock, Philipp; Moeremans, Boaz; Baimpos, Theodoros; Banquy, Xavier; Renner, Frank Uwe; Valtiner, Markus
<x xml:space="preserve">Abstract</x> The importance of water on molecular ion structuring and charging mechanism of solid interfaces in room temperature ionic liquid (RTIL) is unclear and has been largely ignored. Water may alter structures, charging characteristics, and hence performance at electrified solid/RTIL interfaces and is utilized in various fields including energy storage, conversion, or catalysis. Here, atomic force microscopy and surface forces apparatus experiments are utilized to directly measure how water alters the interfacial structuring and charging characteristics of [C2mim][Tf2N] on mica and electrified gold surfaces. On hydrophilic and ionophobic mica surfaces, water‐saturated [C2mim][Tf2N] dissolves surface‐bound cations, which leads to high surface charging and strong layering. In contrast, layering of dry RTIL at weakly charged mica surfaces is weakly structured. At electrified, hydrophobic, and ionophilic gold electrodes, significant water effects are found only at positive applied electrochemical potentials. Here, the influence of water is limited to interactions within the RTIL layers, and is not related to a direct electrosorption of water on the polarized electrode. More generally, the results suggest that effects of water on interfacial structuring of RTIL strongly depend on both (1) surface charging mechanism and (2) interfacial wetting properties. This may greatly impact utilization/design of RTILs and surfaces for interface‐dominated processes.